2022
DOI: 10.1016/j.jpsychires.2022.01.048
|View full text |Cite
|
Sign up to set email alerts
|

Concerns about the social climate, finances, and COVID-19 risk on depression and anxiety: An analysis on U.S. young adults across two waves

Abstract: Concerns regarding contracting COVID-19 and finances may be risks to mental health during the COVID-19 pandemic. Social climate concerns may be another risk, given U.S. protests taking place during this period. We tested the hypothesis that concerns about COVID-19 risk, finances, and social climate would predict clinically significant levels of depression, anxiety, and comorbid depression and anxiety in young adults. 782 U.S. young adults (18–30 years), initially recruited through convenience sampling (social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
2
6
0
Order By: Relevance
“…These challenges are likely to persist for some time as the pandemic continues to ravage the global economy and disrupt the lives of people in Vietnam and around the world (Liu, Wong, & Hyun, 2022). We also confirmed these arguments in a case study in Vietnam (see Appendix…”
Section: Figure 4 Is About Heresupporting
confidence: 76%
See 1 more Smart Citation
“…These challenges are likely to persist for some time as the pandemic continues to ravage the global economy and disrupt the lives of people in Vietnam and around the world (Liu, Wong, & Hyun, 2022). We also confirmed these arguments in a case study in Vietnam (see Appendix…”
Section: Figure 4 Is About Heresupporting
confidence: 76%
“…The younger group [18-34 age], characterized by low saving rates and working in heavily impacted sectors (i.e., tourism and the gig economy), suffers more in terms of wage reductions, food shortages, and financial hardship (compared to middle age group [35-64 age]) (Gould & Kassa, 2020). Meanwhile, the impact of social distancing on the elderly group [65+ age] is a combination of (i) suffering more damage to manual and traditional livelihoods, which were already difficult to carry out before the pandemic, and (ii) less impact on those with savings and retirement income (Liu et al, 2022).…”
Section: The Linkage Between Social Distancing and Economic Performancesmentioning
confidence: 99%
“…The use of the Photovoice methodology creates a space for critical reflection through participatory approaches, which favours, in informal contexts, the development of group resilience by affecting emotional, behavioural and psychological aspects, thereby mitigating the emotional impact of uncertain and highly traumatic situations, such as living with COVID-19. Even during COVID-19, individual and group resilience emerged in dealing with this difficult situation (Novins et al, 2021 ), which led to the identification of strategies to mitigate the impact of the pandemic and to promote coping and well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these are the reason why empowerment plays an important role in crisis such as the Covid-19 pandemic. Coronavirus disease has a lot of critical consequences, developing depression or anxiety symptoms (Glowacz & Schmits, 2020 ; Rania et al, 2021a ) and the literature has shown that there has been a considerable increase in psychological stress among young people (Jackson & Lee Williams, 2022 ) with increased symptoms of anxiety and depression (Adams et al, 2022 ); furthermore, research carried out by Liu et al ( 2022 ) highlighted that both during the first and the second pandemic 41% of young adults reported depressive symptoms and 47 anxiety. In this kind of situation, empowerment plays an important role and comes from the broader context.…”
Section: Introductionmentioning
confidence: 99%
“…Pandemic-related stressors such as threat and risk of contagion, social exclusion, confinement, and uncertainties and worries about the future have been linked to mental health problems (Conrad et al, 2021; Hamouche, 2020; Imran et al, 2020; Liu et al, 2020). Based on a longitudinal study, young adults residing in the United States showed high levels of depressive and anxiety symptoms consistently from 2020 to 2021 (Liu et al, 2022). Despite the pandemic’s negative impact on psychological well-being, prior research suggests that such adverse events can also engender adaptive psychological changes.…”
mentioning
confidence: 99%